2021
DOI: 10.18632/aging.203201
|View full text |Cite
|
Sign up to set email alerts
|

miR-let-7c-5p and miR-149-5p inhibit proinflammatory cytokine production in osteoarthritis and rheumatoid arthritis synovial fibroblasts

Abstract: Osteoarthritis (OA) and rheumatoid arthritis (RA) are two of the most common types of arthritis. Both are characterized by the infiltration of a number of proinflammatory cytokines into the joint microenvironment. miRNAs play critical roles in the disease processes of arthritic disorders. However, little is known about the effects of miRNAs on critical inflammatory cytokine production with OA and RA progression. Here, we found higher levels of proinflammatory cytokines including interleukin 1 beta (IL-1β), int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In addition, osteoblast-synthesized VEGF enhances EPC angiogenesis during RA progression [7], while we have previously demonstrated that S1P stimulates IL-1β production through the JAK and STAT3 signaling pathways in osteoblasts [20], and the S1P/S1P receptor axis reportedly promotes cyclooxygenase-2 and prostaglandin E2 in RA [21]. Previous research has shown that microRNAs (miRNAs) regulate the progression of RA [22,23], and we have reported miRNA involvement in inflammation and angiogenesis [16,24,25]. Notably, S1P can regulate miRNA expression in human disorders such as cancer and rheumatic disease [26][27][28].…”
Section: Introductionmentioning
confidence: 95%
“…In addition, osteoblast-synthesized VEGF enhances EPC angiogenesis during RA progression [7], while we have previously demonstrated that S1P stimulates IL-1β production through the JAK and STAT3 signaling pathways in osteoblasts [20], and the S1P/S1P receptor axis reportedly promotes cyclooxygenase-2 and prostaglandin E2 in RA [21]. Previous research has shown that microRNAs (miRNAs) regulate the progression of RA [22,23], and we have reported miRNA involvement in inflammation and angiogenesis [16,24,25]. Notably, S1P can regulate miRNA expression in human disorders such as cancer and rheumatic disease [26][27][28].…”
Section: Introductionmentioning
confidence: 95%
“…This effect of HO-1 on HCV replication might be explained partly by the iron dependent inactivation of the HCV RNA polymerase NS5B [ 157 ], and by the BV mediated inhibition of HCV NS3/4A protease and induction of an antiviral response by IFNα2 and IFNα17 [ 153 , 158 ]. Moreover, overexpression of miR-let-7c, which interferes with the production of proinflammatory cytokines in osteoarthritis and rheumatoid arthritis synovial fibroblasts [ 159 ], can reduce HCV replication by targeting HO-1 transcriptional repressor Bach1 [ 160 ].…”
Section: Unveiling How Ho-1 Promotes Viral Clearancementioning
confidence: 99%
“…In ammatory factors were increased in patients with obesity [33,34] . Conversely, IL-13 and IL-33, which are anti-in ammatory cytokines, were decreased in obesity [35] . A high-fat diet with IL-33 injection improved insulin sensitivity in an animal study, which indicated that anti-in ammatory treatment could decrease insulin resistance in obesity [35,36] .…”
Section: Validation Of Obesity-related Ncrnas In the Cerna Networkmentioning
confidence: 89%
“…Conversely, IL-13 and IL-33, which are anti-in ammatory cytokines, were decreased in obesity [35] . A high-fat diet with IL-33 injection improved insulin sensitivity in an animal study, which indicated that anti-in ammatory treatment could decrease insulin resistance in obesity [35,36] . In this study, KEGG enrichment showed that pathways including cytokine-cytokine receptor interactions, and TNF and NF-kappa B pathway signaling, regulated obesityrelated in ammation and insulin resistance [37][38][39] .…”
Section: Validation Of Obesity-related Ncrnas In the Cerna Networkmentioning
confidence: 89%